Pregnancy rate after estrus synchronization and timed artificial insemination in Mediterranean buffaloes in two seasons in Venezuela - Miguel Chacón; Néstor Morán; Iván Cárdenas; Mariana S. Perea; Fernando P. Perea; Aitor De Ondiz (Revista Científica)
A retrospective study (2016-2018) was conducted in a commercial farm from Zulia state, Venezuela, to analyze the effectiveness of ovulation synchronization followed by fixed-time artificial insemination (TAI) at two seasons of the year: 1) May-September [unfavorable (U), n=386] 2) October-December [favorable (F), n=308]. A total of 694 ovulation synchronization protocols were applied in 190 heifers- and 504 cow-buffalos. In season U, an intravaginal device (IVD) was used for 9 days (day 0: IVD + 2 mg estradiol benzoate; day 9: 200-230 IU eCG; day 11: 1 mg GnRH) and TAI at 64-66 hours post IVD removal. Ovsynch (IATF 16 to 18 hours after the second GnRH injection) or IVD protocols were used in season F. Calving to synchronization interval was 102.2 ± 51.8 and 126.0 ± 74.8 days for seasons U and F, respectively. Data were analyzed by the Chi-square test of SAS. Pregnancy rate (pregnant buffaloes divided by inseminated buffaloes after ovulation synchronization × 100) did not vary between seasons: 43% (166/386) and 45.8% (141/308) for U and F, respectively (p>0.05). In season U, buffalo heifers had a pregnancy rate of 50.8% (62/122) and buffalo cows 39.9% (104/264) (p<0.05). In season F, the pregnancy rate was similar between groups: 44.1% (30/68) and 46.2% (111/240) for heifers and buffalo cows, respectively (p>0.05). In this tropical buffalo herd, the pregnancy rate after IATF was comparable between seasons; however, in the unfavorable season, buffalo heifers were more fertile than buffalo cows.